Biostatistical Approach to Predict Disease Risk Using Public Health Data - Loso Judijanto; Isah Fitriani (PT. Anagata Sembagi Education, 2026)
The increasing complexity of public health issues demands an analytical approach capable of optimally utilizing data to support disease prevention efforts. The increasing availability of public health data opens up opportunities for the development of evidence-based predictive approaches. This study aims to examine the role of biostatistical approaches in predicting disease risk using public health data and its implications for preventive efforts and health policy. The study employed a qualitative approach using literature review methods, including journal articles, academic books, and relevant policy documents. Data analysis was conducted thematically to identify the role of biostatistics in risk factor analysis, predictive model development, and the associated methodological and policy challenges. The study results indicate that biostatistical approaches play a crucial role in identifying multifactorial relationships between health determinants and disease incidence at the population level. Disease risk prediction models have been shown to support the identification of high-risk groups and the planning of more efficient preventive interventions. Key challenges include data quality, limited human resources, and gaps in the translation of analysis results into health policy. Overall, the biostatistical approach is a strategic foundation for the development of a data- and evidence-based public health system oriented towards disease prevention